FORMATION OF SPECIAL COMPETENCIES OF LAW STUDENTS FOR WORK IN ECONOMIC FIELD - Bobkova, Antonina; Zakharchenko, Andrii; Lypnytska, Yevheniia; Pavliuchenko, Yuiliia; Lekhkodukh, Inna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The aim of the research paper is to suggest the proposals on improving approaches to the formation of special competencies of law students for their preparedness to legal support of economic activity. The article focuses on the shortcomings of the legal education system, which lay in the lack of applied skills of the graduate students, as well as their insufficient ability to apply theoretical knowledge, which they acquired, in practice. One of the reasons for this state of training of future lawyers is the predominance of traditional forms of teaching specialized legal disciplines. The study concluded that the list of special competencies contained in The Standard of higher education of Ukraine on specialty «Law» was not sufficiently specific, because it does not focus on the competencies, directed specifically to work in economic field. Based on the analysis of the specialties of legal practice in economic field, a basic list of such special competencies is proposed. One of the ways of forming special competencies of law students using the method of analysis of video recording of the broadcast of trial proceedings on the example of the academic discipline «Economic Procedural Law» is illustrated in the paper.